An Apriori algorithm-based association rule analysis to identify acupoint combinations for treating uremic pruritus - Ping-Hsun Lu; Chien-Cheng Lai; Ling-Ya Chiu; I-Hsin Lin; Chih-Chin Iou; Po-Hsuan Lu (Tzu Chi Medical Journal)
Objective: Uremic pruritus (UP) is a prevalent and troublesome condition affecting individuals with end-stage renal failure, which results in intense pruritus, depression, as well as poor quality of sleep, significantly impacting their quality of life. According to previous studies, acupuncture and acupoint stimulation have been shown to provide additional benefits in treating UP in dialysis patients. In addition, using acupoints combination may yield superior effectiveness compared to utilizing a singular acupoint. To investigate the potential correlations between acupoint combinations, an association-rule analysis was employed. Materials and Methods: Apriori algorithms stand out as highly potent techniques for identifying associations in databases; this study utilized an association rule mining to examine the association rules of key acupoint groupings that could be employed for treating UP. Results: The analysis utilized information derived from the meta-analysis encompassing 40 randomized controlled trials that used acupuncture to treat UP. In total, 64 acupoints were analyzed, and 71 association rules were found. The following acupoint combinations: Auricular shenmen (TF4), Quchi (LI11), and Geshu (BL17); Auricular heart (Extra14), Sanyinjiao (SP6), and Auricular lung (CO14); and Auricular heart (Extra14), Xuehai (SP10), and Auricular lung (CO14) showed the strongest associations. Conclusion: Acupoints involving Auricular shenmen (TF4), Quchi (LI11), Geshu (BL17), Auricular heart (Extra14), Sanyinjiao (SP6), Auricular lung (CO14), and Xuehai (SP10) can be regarded as the core combination of acupuncture points for managing UP.